2015
DOI: 10.5152/iao.2015.752
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Protective Effects of 2-aminoethyl Diphenylborinate against Inner Ear Acoustic Trauma: Experimental Study Using Transmission and Scanning Electron Microscopy

Abstract: OBJECTIVE:In this prospective experimental study, we investigated the preventive effects of 2-aminoethyl diphenylborinate (2-APB) in rats exposed to acoustic trauma (AT). Light microscopic, transmission electron microscopic (TEM), and scanning electron microscopic (SEM) examinations were performed. MATERIALS and METHODS:Eighteen healthy Wistar albino rats were divided into the following three groups: groups 1 (control), 2 (AT), and 3 (AT+APB). The rats in groups 2 and 3 were exposed to AT; in group 3 rats, 2-A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Similarly, other authors [17] observed extensive damage, loss of stereocilia and holes in the apical membranes of OHCs and IHCs originated from the bursting of blebs formed at the apical pole of the stressed hair cells to release cellular material into the endolymphatic compartment. They observed these findings by SEM and TEM examination after acoustic trauma.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Similarly, other authors [17] observed extensive damage, loss of stereocilia and holes in the apical membranes of OHCs and IHCs originated from the bursting of blebs formed at the apical pole of the stressed hair cells to release cellular material into the endolymphatic compartment. They observed these findings by SEM and TEM examination after acoustic trauma.…”
Section: Discussionmentioning
confidence: 54%
“…due to noise over stimulation causes increased resistance in the vascular smooth muscle cells that can lead to cochlear damage due to the vasoconstriction of SMA [17] .…”
Section: Discussionmentioning
confidence: 99%
“…Hence, if abnormal changes occur in the SMA, such as vasospasm, this change would reduce or even completely interrupt the cochlear blood supply. This condition contributes to blood circulation disorders in the inner ear and cochlear dysfunction, such as dizziness, tinnitus, and other symptoms [8,10]. Hence, the blood supply of SMA may have a decisive impact on maintaining normal hearing [11].…”
Section: Introductionmentioning
confidence: 99%